How to do (or not to do)… Measuring health worker motivation in surveys in low- and middle-income countries - Borghi, Josephine; Lohmann, Julia; Dale, E.; Meheus, F.; Goudge, J.; Oboirien, K.; Kuwawenaruwa, A. (Health policy and planning, 2018)
A health system’s ability to deliver quality health care depends on the availability of motivated health workers, which are insufficient in many low income settings. Increasing policy and researcher attention is directed towards understanding what drives health worker motivation andhow different policy interventions affect motivation, as motivation is key to performance andquality of care outcomes. As a result, there is growing interest among researchers in measuringmotivation within health worker surveys. However, there is currently limited guidance on how toconceptualize and approach measurement and how to validate or analyse motivation data collected from health worker surveys, resulting in inconsistent and sometimes poor quality measures.This paper begins by discussing how motivation can be conceptualized, then sets out the steps indeveloping questions to measure motivation within health worker surveys and in ensuring dataquality through validity and reliability tests. The paper also discusses analysis of the resulting motivation measure/s. This paper aims to promote high quality research that will generate policy relevant and useful evidence.
Published: 20 November 2017
Gesehen am 31.03.2020